Landmark-based geometric morphometrics analysis of body shape variation among populations of the blue jack mackerel, Trachurus picturatus, from the North-East Atlantic - Moreira, Cláudia; Froufe, Elsa; Vaz-Pires, Paulo; Triay Portella, Raül; Correia, Alberto Teodorico (Journal of Sea Research, 2020)
Phenotypic variation in fish can indicate exposure to different environmental conditions, affecting species growth and maturation rates and/or be a consequence of genetic factors that allow fish adaptation to different environments. Understanding population structure and dynamics is extremely important for the establishment of sustainable fisheries. The blue jack mackerel, Trachurus picturatus, is an important fishery resource of the North-East (NE) Atlantic. Fish were captured in six sampling locations in the NE Atlantic - Azores, Madeira, Canaries and Portugal mainland - Matosinhos, Peniche and Portimão. The phenotypic diversity of the species was studied using body landmark-based geometric morphometrics. A truss box method was followed and 30 distance variables were extracted from digital images. Additionally, the temporal stability of the morphological characters was investigated by comparing samples from two different years: 2016 and 2019. The transformed distances were analysed by univariate and multivariate statistics. The Macaronesia region – Azores, Madeira and Canaries – and Portugal mainland displayed a clear phenotypic pattern. Distances related to the body width and caudal peduncle were the most significant variables explaining the observed phenotypic heterogeneity. Furthermore, this study also showed that T. picturatus can exhibit fast phenotypic adaptations to the surrounding environment, observed by the discrimination of Peniche in 2019. Nevertheless, the high overall allocation of individuals to the original location observed for both years (78% in 2016 and 83% in 2019) suggests that the population of T. picturatus in the NE Atlantic is phenotypic heterogeneous. These findings corroborate previous studies and have implications for fishery management. 0,719 2,108 Q2 Q2 SCIE